2016
DOI: 10.1002/cssc.201600674
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Pressure Vapor‐Assisted Solution Process for Thiocyanate‐Based Pseudohalide Perovskite Solar Cells

Abstract: In this report, we fabricated thiocyanate-based perovskite solar cells with low-pressure vapor-assisted solution process (LP-VASP) method. Photovoltaic performances are evaluated with detailed materials characterizations. Scanning electron microscopy images show that SCN-based perovskite films fabricated using LP-VASP have long-range uniform morphology and large grain sizes up to 1 μm. The XRD and Raman spectra were employed to observe the characteristic peaks for both SCN-based and pure CH NH PbI perovskite. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 53 publications
(112 reference statements)
2
31
0
Order By: Relevance
“…The replacement of two iodides by SCN − significantly boosted the moisture tolerance ( Figure 16 ). Moreover, Pb(SCN) 2 is much cheaper than PbI 2 . They suggested that the lone pair electrons of the linear shaped SCN − interact more strongly with the Pb ion than that of the spherical I − , which is beneficial for stabilizing the PVSK structure.…”
Section: X‐site Mixed Pvskmentioning
confidence: 59%
“…The replacement of two iodides by SCN − significantly boosted the moisture tolerance ( Figure 16 ). Moreover, Pb(SCN) 2 is much cheaper than PbI 2 . They suggested that the lone pair electrons of the linear shaped SCN − interact more strongly with the Pb ion than that of the spherical I − , which is beneficial for stabilizing the PVSK structure.…”
Section: X‐site Mixed Pvskmentioning
confidence: 59%
“…As the perovskite film thickness increases, the short circuit current density ( J SC ) is enhanced due to augmented photonic absorption ( Figure and Figure S2b, Supporting Information). A small change in J SC is due to the J SC having already reached almost maximum photocurrent density of MAPbI 3 based perovskite solar cell (≈22.61 mA cm −2 ) . Because the fabricated perovskite films have enough thickness (400–900 nm) to absorb incident light.…”
Section: Resultsmentioning
confidence: 99%
“…The inset in Figure a is the equivalent circuit employed to fit the spectra . In the equivalent circuit, a series resistance ( R s ) is used to model the interface resistance of the ITO substrate, and the interface of the selective contacts (SCs) with the perovskite layer are represented by the SC resistance ( R sc ) and SC capacitance ( C sc ) components . R rec and C ps are the recombination resistance and the perovskite layer capacitance, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…Robert L. Z. Hoye et al explored methylammonium bismuth iodide as a lead-free, stable hybrid organicinorganic solar absorber [318,319] . Replacing chemical reactive halide ions with more robust pseudohalogen polyanions appears to be a promising approach for enhancing the chemical stability of perovskites [320][321][322][323][324][325][326] . Tao Xu et al [322] replaced two iodides in CH 3 NH 3 PbI 3 by two pseudohalide thiocyanate ions (SCN -) to form CH 3 NH 3 Pb(SCN) 2 I.…”
Section: Perovskite Materials Modificationmentioning
confidence: 99%